2006
DOI: 10.1051/0004-6361:20053405
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the cyclic modulation of photospheric lines

Abstract: We have studied the behavior of three photospheric lines (Fe I 537.9, C I 538.0 and Ti II 538.1 nm), which have been monitored on the Sun for more than twenty years, either as full-disk or as center-disk measurements (Gray & Livingston 1997;Livingston & Wallace 2003). The aim is to detect a possible photospheric variation with the cycle. We try to reconstruct the cyclic variations of full-disk line depths as due to active region (AR) modulation through a spectral synthesis with FAL semi-empirical models (Fonte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 26 publications
2
26
0
Order By: Relevance
“…Earlier results obtained with both a regression method and a semi-empirical model were presented by, e.g. Penza et al (2003Penza et al ( , 2006, Domingo et al (2009) and Ermolli et al (2011). A new semi-empirical model, briefly outlined below, is currently under development (Ermolli et al, 2012).…”
Section: Oarmentioning
confidence: 94%
“…Earlier results obtained with both a regression method and a semi-empirical model were presented by, e.g. Penza et al (2003Penza et al ( , 2006, Domingo et al (2009) and Ermolli et al (2011). A new semi-empirical model, briefly outlined below, is currently under development (Ermolli et al, 2012).…”
Section: Oarmentioning
confidence: 94%
“…The quasi-biennial component of the solar cycle, although weaker than the main one, is very robust since it has been recorded by many indicators (see e.g. Kane 2005;Penza et al 2006;Li et al 2006;Cadavid et al 2005). The peak in P j (T ) corresponding to the short-term contribution, although significant, is underestimated compared to the main cycle peak.…”
Section: Time Evolution Of Pod Coefficients: Wavelet Analysis and Permentioning
confidence: 99%
“…Gnevyshev 1977;Rusin & Zverko 1990;Bay 2003;Kane 2005;Vecchio et al 2005;Penza et al 2006). Among the yearly periodicities, the most noticeable periods are 1.3 years and 3.6 years, along with some periods in the range between 2.6 years and 2.8 years (for a complete classification of the high-frequency periodicities observed in many solar indices see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Livingston et al (2007) could not confirm this finding in the next solar cycle for the unblended strong Fe I and the Na I D lines. This is, probably, a good indication of how challenging such observations are (see also discussion in Penza et al 2006). Instead, Livingston et al (2007) reported cyclic variation in the Mn I 539.4 nm line and the CN 388.3 nm bandhead.…”
Section: Introductionmentioning
confidence: 97%